Impact of pure desmoplastic histological growth patterns in colorectal liver metastasis - Chie Takasu; Yuji Morine; Kozo Yoshikawa; Takuya Tokunaga; Masaaki Nishi; Hideya Kashihara; Yuma Wada; Toshiaki Yoshimoto; Mitsuo Shimada (BMC Cancer)
Abstract Background Colorectal cancer (CRC) has increasingly come into worldwide cancer and almost half of patients have liver metastasis (CRLM) during the progression. Therefore, treatment of colorectal cancer liver metastasis (CRLM) is important to improve the prognosis of CRC patients. Histopathological growth patterns (HGPs) of CRLM have emerged as a reliable prognostic marker. In this study, we investigated the role of prognostic impact of pure desmoplastic HGPs (dHGPs), 100% desmoplastic, in CRLM. Methods The present study evaluated the HGPs in 71 patients with CRLM who underwent surgery (R0) between 1995 and 2012. HGPs were classified by international consensus guidelines with H&E stained slides. The pure dHGPs was defined as a complete peripheral fibrotic rim around the tumor. Results The dHGP was present in 36.6% (n = 26) and the pure-dHGPs was present in 73% (n = 19) among dHGPs patients. Pure-dHGPs were significantly associated with sex (male), metachronous metastatic period, normal CEA level, shallow tumor invasion and less lymph node metastasis. Patients with dHGPs had longer overall survival (OS) compared to other HGPs (p < 0.05). Furthermore, pure dHGPs patients had longer OS than non-pure dHGPs (90.9% vs. 51.4%, p < 0.05). Multivariate analysis identified pure dHGPs (p = 0.04) and better primary tumor differentiation (p < 0.001) were identified as independent prognostic indicators for OS. Patients with pure dHGPs also had longer disease-free survival (DFS) compared to other HGPs (p < 0.05). Pure-dHGPs patients had longer DFS than non-pure dHGPs (63.4% vs. 28.8%, p < 0.05). Multivariate analysis identified pure dHGPs (p = 0.04) and better primary tumor differentiation (p = 0.03) as independent prognostic indicators. Conclusions Pure desmoplastic HGP might be a good prognostic marker in CRLM.